Fetal hepatic tumors, apropos of a case of giant hemangioendothelioma - Lacunza Paredes, Rommel Omar (2020)
Case report of a giant fetal hepatic tumor diagnosed in the third trimester of pregnancy that presented signs of imminent cardiac failure. Postnatal tests confirmed the suspicion of hepatic hemangioma. Currently, the patient is under expectant management, evolving towards regression. We review the characteristics of the main fetal primary liver tumors.